THE HUMOROUS EFFECTS IN POLITICAL DISCOURSE DURING INTERVIEWS: RHETORIC, PERFORMANCE, AND DEMOCRATIC AMBIVALENCE IN THE CASE OF DONALD TRUMP’S 2025 SPEECH - Azimova Marjona Salim qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article develops a theoretically grounded and discourse- analytical account of humor in contemporary political interviews, situating Donald Trump’s 2025 interview speech within broader transformations of mediated political communication. Drawing on classical rhetoric, Bakhtinian carnivalesque theory, psychoanalytic relief theory, and Goffman’s dramaturgical sociology, the paper conceptualizes political humor as a multifunctional discursive mechanism operating at the intersection of persuasion, identity construction, affect regulation, and accountability management. Through comparative analysis with interview performances by Barack Obama and Volodymyr Zelenskyy, the study proposes a typology of dominance, self-reflexive, and solidaristic humor. It argues that humor in political interviews constitutes a form of “affective governance” that simultaneously intensifies political engagement and destabilizes deliberative norms.